2019
DOI: 10.1111/jace.16735
|View full text |Cite
|
Sign up to set email alerts
|

The role of diffusion behavior on the formation and evolution of the core‐shell structure in BaTiO3‐based ceramics

Abstract: In this work, the influence of starting particle size and sintering conditions on the microstructures and dielectric properties of BaTiO3‐based ceramics coated with 0.3Bi(Zn1/2Ti1/2)O3‐0.7BaTiO3 were investigated to reveal the core‐shell structure by using high resolution transmission electron microscopy technique coupled with energy‐dispersive spectrometer analysis. The ion‐diffusion behavior plays a critical role in the formation and evolution of the core‐shell structure and, therefore, significantly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The BT‐based core‐shell structure consists of the compositional gradient regions with different properties, and the BT‐based nanoparticles are usually coated by insulating dielectrics (eg, SiO 2 , Al 2 O 3 , ZrO 2 , MgO). Then the diffused ε r ‐ T curves and improved BDS can be observed, which can significantly facilitate the dielectric temperature stability and boost the superior energy storage performance 216,217 . The introduction of porosity into ferroelectric ceramics can usually decrease the permittivity due to the ceramic‐air composite, which helps to optimize the performances of pyroelectric thermal detector, pyroelectric/piezoelectric energy harvesting, and piezoelectric acoustic sensors, etc 218‐220 .…”
Section: Structure Design For Properties Improvementmentioning
confidence: 99%
“…The BT‐based core‐shell structure consists of the compositional gradient regions with different properties, and the BT‐based nanoparticles are usually coated by insulating dielectrics (eg, SiO 2 , Al 2 O 3 , ZrO 2 , MgO). Then the diffused ε r ‐ T curves and improved BDS can be observed, which can significantly facilitate the dielectric temperature stability and boost the superior energy storage performance 216,217 . The introduction of porosity into ferroelectric ceramics can usually decrease the permittivity due to the ceramic‐air composite, which helps to optimize the performances of pyroelectric thermal detector, pyroelectric/piezoelectric energy harvesting, and piezoelectric acoustic sensors, etc 218‐220 .…”
Section: Structure Design For Properties Improvementmentioning
confidence: 99%
“…The diffusion proceeds as the sintering temperature increases. 21,22) In this study, Dy could diffuse more in lot A than lot B, sintered at higher temperature.…”
Section: Microstructural Design For Higher Reliability Of Mlccsmentioning
confidence: 62%
“…9) Several studies have shown that suitable ion dopant in BaTiO 3 reduced mobile oxygen vacancies. 8,9) Various analysis techniques have been used for evaluation of core-shell structure, site occupancy of additive ions, and electric properties related to these microstructures, such as X-ray diffraction, [11][12][13][20][21][22] transmission electron microscope (TEM), 9,10,[21][22][23] differential scanning calorimetry, 12,13,21) thermally stimulated depolarization current, 8,9) I-V characteristics, 9,19) temperature coefficient of capacitance, 9,13,22,24) and impedance spectroscopy. [9][10][11]19,25) While the relationship between the average microstructures and the reliability has been investigated, our group has developed the technique to fabricate 'prebreakdown' MLCCs and to identify the degraded area without catastrophic changes, 26) for clear understanding of the degradation mechanism of MLCCs.…”
Section: Introductionmentioning
confidence: 99%
“…In the quest to enhance the voltage and temperature stability of ceramic dielectrics, two commonly employed methods are the core-shell structure and the relaxation dispersion approach, illustrated in Figure 1B and C, respectively. The implementation of a core-shell structure aims to optimize dielectric temperature stability, 4,5 as depicted in Figure 1B. This structural configuration involves core and shell regions with distinct polarization levels, leading to separated dielectric peaks across the temperature range of interest.…”
Section: Introductionmentioning
confidence: 99%